#MeToo and broadcast journalism in South Korea: The gatekeeping process of #MeToo. Issue 3 (1st November 2019) - Lee, Misook
This article aims to articulate the process of broadcasting #MeToo in South Korea to understand the gatekeeping process and its impact on the expansion of the #MeToo movement. After Suh Ji-hyun, a prosecutor, spoke out publicly about her experiences of being sexually harassed, South Korea has witnessed the expansion of #MeToo and #WithYou, a solidarity movement with the victims, in every sector of society. To understand how a gendered and patriarchal society could bring huge support for the #MeToo, this article sheds light on the broadcasting process of #MeToo. The most trusted and influential news brand in South Korea is JTBC, a TV broadcasting company. This research conducted semi-structured interviews with JTBC journalists and analysed the content of the JTBC news. JTBC put higher news value on 'victim's voices' delivered directly through TV live interviews and framed #MeToo as a 'structural problem' from the power relation. Through interviews with journalists, this research found that #MeToo stories could pass through the individual, organizational and social-system level, which made the intensive media coverage on #MeToo possible and eventually developed the expansion and impact of #MeToo among society including media organizations reflexively.